Resiliensi Perempuan dalam Konflik Lingkungan di Indonesia - Mustofa, Mustabsyirotul Ummah; Raudya, M. Diva Kafila; Langit, Jian Ayune Sundul; Biworo, Pupoes (Journal of Political Issues, 2023)
Environmental conflict is a problem often found in various regions in Indonesia, which occurred in Kendeng and Sangihe. If we look at the impact of environmental conflicts, this threatens the whole community regardless of the gender contained in the object of the dispute. Even so, environmental conflicts are often identified as something “masculine”. This study seeks to describe how women’s resilience in environmental conflicts that occurred in Kendeng and Sangihe. Besides that, this research also seeks to see how the various narratives of ecofeminism relate to the resilience practices carried out by women in the context of environmental conflicts. The researcher uses a qualitative research type with the unit of analysis of two Watchdoc documentaries entitled “Samin vs Semen” and “Sangihe Melawan” which will be analyzed using content analysis techniques. The results of the study show that the role of women in the movement against environmental conflict in both Kendeng and Sangihe is determined by a sense of ownership of the environment or nature which is a means of fulfilling the material needs of the local community. Another research result is that there are differences in the narratives of ecofeminism contained in the two movements, with the movement in Kendeng which is more towards spiritual ecofeminism and the movement in Sangihe which is more towards transformative ecofeminism. Although there are differences in terms of ecofeminism narratives, there are no significant differences in terms of resilience practices carried out by women in both Kendeng and Sangihe.